(untitled) (Revista Innova Educación, 2019)
The objective of this paper was to analyze and interpret the poem "En la calle" by José Paniagua Núñez. The research method was hermeneutics and the technique was Discourse Analysis, for which the following dimensions were considered: a) textual dimension, b) semiotic dimension, c) enunciative dimension and d) pragmatic dimension. "En la calle" is a linguistic construction that meets the criteria of textuality. At a semiotic level, "En la calle" implies that the street itself is an element that lives and feels along with the author the inevitable passage of time, evoking memories and sensations with which he projects his longing. At the enunciative level, Paniagua expresses himself in the first person, including the street itself, it is not an "I" but "we", while expressing feelings full of subjectivity and reflection. Finally, at the pragmatic level, the enunciator complies with transmitting ideas to the reader or listener with the intention of producing reflection.